1999
DOI: 10.1177/136216889900300204
|View full text |Cite
|
Sign up to set email alerts
|

A community of learners: Cambodians in an adult ESL classroom

Abstract: This article focuses on the English literacy development of Cambodian adults living in the United States. Using an adult ESL classroom as a c o n t e x t , the researcher describes: how the Cambodian adults, literate in K h m e r, participate in each other's English literacy development; h o w Cambodian children, fluent though not typically literate in Khmer, participate in their parents' development of English literacy ; and how a Cambodian teacher participates in his students' development of English literacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…To enable this, teachers can group students with shared languages together (Chau, 2007;Goldstein, 2003) and explicitly support home language use in collaborative activities (Goldstein, 2003;Mohanty et al, 2010). Teachers can also engage students as classroom experts (Hardman, 1999), inviting them to co-teach, translate, translanguage, or present in home language (García, Flores, & Woodley, 2012).…”
Section: Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable this, teachers can group students with shared languages together (Chau, 2007;Goldstein, 2003) and explicitly support home language use in collaborative activities (Goldstein, 2003;Mohanty et al, 2010). Teachers can also engage students as classroom experts (Hardman, 1999), inviting them to co-teach, translate, translanguage, or present in home language (García, Flores, & Woodley, 2012).…”
Section: Participationmentioning
confidence: 99%
“…Students can create translanguaging texts, as in Schwinge's (2003) example of home language speech bubbles alongside English language stories. Additionally, students can share feedback and explain corrections multilingually in peer drafting activities (de Jong & Freeman Field, 2010;Hardman, 1999).…”
Section: Language and Literacymentioning
confidence: 99%
“…A growing number of researchers are investigating this community and their learning needs, most notably the Low Educated Second Language and Literacy Acquisition Symposium, which meets yearly to share research and develop plans to better serve this community. Many suggest that learners are to be instructed in phonics and sound–letter correspondences (Hardman, ; Haverson & Haynes, 1982; Shaughnessy, ), and best practices include explicitly teaching word recognition and alphabetic print literacy(Bigelow & Schwarz, ; Bigelow & Vinogradov, ; Burt, Peyton, & Schaetz, 2008).…”
Section: Current Approaches To Teaching Refugeesmentioning
confidence: 99%
“…Others stress the need to look at the diversity of bilingual and multilingual educational settings in order to get a better grasp on the benefits and challenges of language learning (Hélot & de Mejía, 2008). This includes English language learning settings, where studies have found benefits in utilizing and valuing students' first languages in the classroom (Hardman, 1999;Lucas & Katz, 1994;Malicky & Derwing, 1993).…”
Section: Ideologies Of Mono-and Bilingualism In the Language Learningmentioning
confidence: 99%
“…It has been pointed out that discussion around bilingual education and ideologies must focus not only on institutions and students, but also teachers. Having not only a space for bilingual learning but also bilingual instructors is something that is important (Hardman, 1999). In addition, it is important to understand teachers' ideologies of learning and language and for teachers to be reflective of this in order to create spaces for agency and change (Pease-Alvarez et al, 2010).…”
Section: Ideologies Of Mono-and Bilingualism In the Language Learningmentioning
confidence: 99%